Nations and households in economic growth : essays in honor of Moses Abramovitz - David, Paul A.; Reder, Melvin Warren (New York : Academic Press, 1974)
The book is a joints efforts of individual contributors which reflects the broad sweep of Abramovit'z recent interests within the discipline of economics and economic theory.in celebration of Moses Abramovit'z sixtieth birthday, on January1, 1972.
Includes index.
Includes bibliographical references: p. 405-406.
gp 24/01/2019
Loans
Keywords: Abramovitz, Moses; Microeconomics; Macroeconomics; Economic policy